Variación diurna de la radiación solar global ultravioleta con la altitud geográfica en Costa Rica (ING) - Wright, Jaime (1993)
Ultraviolet radiation (UV) contributes Little to the solar spectrum; however, it is very important as a result of its strong biological action. Experimental measurements of global and UV radiation were carried out at different altitude stations in Costa Rica (Heredia 1.050m, Volcán Irazú 3.400m, Monte Verde de Siquirres 34m, Limón 5m and San Pablo de Turrubares 375m). The global and UV radiometers were interfaced to a data acquisition system (data logger) in order to read the output every 30 sec during the solar day.In order to determine and analyze peaks of maximum and minimum hourly-averaged radiation in clear sky conditions, global and Uv solar radiation data were processed and measured within the period February 1991 to January 1993 (2 years) in Heredia. Data for the other stations were processed using global and UV solar radiation for several consecutive days in February, March and April of 1992. Hourly and daily variations of global and ultraviolet solar radiation with altitude were also analyzed. Over a two years period in Heredia the computed annual means for the global UV radiation were 0.215Kwh/m2, with a maximum in march of 0.290 Kwh/m2 and a minimum in October of 0.172 Kwh/m2 The hourly percentage of the quotient between ultraviolet Iv and the global radiation Ig (Iv/Ig)x100 varies from a maximum of 4.7% to a minimum of 3.1% in Limón, and from a maximum of 5.2% to a minimum of 3.1% at Volcán Irazú. For all stations it is found an increase of (Iv/Ig)x100 due to increasing cloudiness,  consistent with the known fact that clouds absorb more energy in the near infrared than in the ultraviolet region of the solar spectrum. A similar effect occurs at low solar altitude.Employing the least-square linear regression  analysis an estimated empirical function relating global radiation to ultraviolet radiation was obtained.